2015
DOI: 10.1016/j.tcb.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

YAP and TAZ: a nexus for Hippo signaling and beyond

Abstract: The Hippo pathway is a potent regulator of cellular proliferation, differentiation, and tissue homeostasis. Here we review the regulatory mechanisms of the Hippo pathway and discuss the function of Yes-associated protein (YAP)/transcriptional coactivator with a PDZ-binding domain (TAZ), the prime mediators of the Hippo pathway, in stem cell biology and tissue regeneration. We highlight their activities in both the nucleus and the cytoplasm and discuss their role as a signaling nexus and integrator of several o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
502
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 483 publications
(511 citation statements)
references
References 202 publications
(364 reference statements)
9
502
0
Order By: Relevance
“…7D). The expression of the YAP target gene for amphiregulin (Areg) (41,42) was also significantly increased in crypts of the mutant mice (Fig. 7E).…”
Section: Generation Of Iec-specific Csk Cko Micementioning
confidence: 94%
“…7D). The expression of the YAP target gene for amphiregulin (Areg) (41,42) was also significantly increased in crypts of the mutant mice (Fig. 7E).…”
Section: Generation Of Iec-specific Csk Cko Micementioning
confidence: 94%
“…Wnt5a/b activate noncanonical Wnt signaling by binding to the Frizzled receptors, the class F GPCRs (Anastas and Moon 2013). As both the Hippo pathway and canonical Wnt signaling are master regulators of tissue growth and morphogenesis, cross-talk between the two pathways has been extensively studied and thoroughly summarized by recent reviews (Piccolo et al 2014;Hansen et al 2015). It was recently reported that the noncanonical Wnt ligands Wnt5a/b activate YAP/TAZ through the Gα 12/13 -Rho-LATS signaling axis by binding to the Frizzled receptors .…”
Section: Soluble Factors and G-protein-coupled Receptors (Gpcrs)mentioning
confidence: 99%
“…Although the core Hippo pathway components are conserved, their functions vary in different tissues, contexts and model systems [10]. The LATS kinase phosphorylates and negatively regulates the activity of the transcriptional modulators YAP and tafazzin (TAZ) that are considered as the major transducers of Hippo pathway activity [11]. Although their role as transcriptional co-activators is well established, recently Kim et al have also shown a co-repressor function for YAP and TAZ that promotes cell growth and survival [12].…”
Section: The Hippo Pathway and Cancermentioning
confidence: 99%
“…Deregulation of YAP signaling is associated with several diseases including cancer [16][17][18] and YAP has been considered as an appealing therapeutic target since it is found upregulated in different types of cancers. Also, YAP expression or activation has been shown to correlate with poor disease outcome [11,[19][20]. YAP transcriptional activity is also associated with metastasis of melanoma, lung and breast cancer [21][22][23].…”
Section: The Hippo Pathway and Cancermentioning
confidence: 99%